2022
DOI: 10.1021/acsomega.2c01531
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of a Statistical and Analytical Method to Find the Relationship between the Morphological and Optical Properties of ZnO Nanoflower Arrays

Abstract: In this study, a sapphire substrate with a patterned concave structure was used to prepare ZnO film/A-B glue, and the ZnO film/A-B glue with a patterned convex matrix was transferred onto a silicon wafer using the lift-off technology as the seed layer. Then, the hydrothermal method with different Zn(CH 3 COO) 2 and C 6 H 12 N 4 concentrations as precursors was used to synthesize ZnO nanoflower arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…A square with an area of 1 μm 2 was then drawn around each of the five points, and the number of ZnO nanorods in each square was counted. (13,14) For synthesis times of 30, 45, and 60 min, the average numbers of ZnO nanorods in 1 μm 2 were 125, 116, and 48, respectively. As the growth time increased, the density of ZnO nanorods decreased and the diameter increased.…”
Section: Resultsmentioning
confidence: 97%
“…A significant finding of this research is the development of an inexpensive technique to create a ZnO seed layer with a matrix and protrusion structure for synthesizing ZnO NFAs using a combination of template technology and the hydrothermal method for synthesizing one-dimensional ZnO-based nanomaterials. This approach involves the uses of patterned sapphire as templates and lift-off as the technology to create ZnO NFAs [ 11 , 12 ]. The synthesis results of ZnO NFAs were analyzed by varying the synthesis time while keeping the other parameters constant [ 13 ].…”
Section: Introductionmentioning
confidence: 99%